Kinetic analysis of biohydrogen formation using immobilized hydrogen-producing bacteria on activated carbon sponge from pineapple residues - Nur Kamilah Abd Jalil,; Umi Aisah Asli,; Aidee Kamal Khamis,; Haslenda Hashim,; Johari Kamaruddin,; Mimi Haryani Hassim,; Suleeporn Bunbongkarn Choopavang, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pineapple residues are one of potential biomass feedstock for biohydrogen production. The most convenient way to produce biohydrogen from pineapple residual is through fermentation proses. The process is environmentally friendly and consumes low energy, but generally the process has low yield production. Various strategies can be used to increase production, including the use of immobilized cells in fermentation. The performance of the process can be explained as realistically as possible by the appropriate kinetic model. In this work, a kinetic analysis on fermentative biohydrogen production using different hydrogenproducing bacteria immobilized onto activated carbon sponge has been performed. The performance of cumulative and biohydrogen production rate were assessed using modified Gompertz equation via Excel solver application. All fermentation processes were carried out at a condition of initial pH 7 and temperature of 32 ± 1°C, with 30% v/v inoculum of working volume in batch process. Three different hydrogen-producing bacteria were used, namely Escherichia coli, Enterobacter aerogenes and Clostridium sporogenes, were immobilized onto activated carbon sponge and in free cell form as comparison. Based on best fitting curve results on the cumulative biohydrogen production, it was found that modified Gompertz equation were fitted well with all the experimental results of all regression values, R2 were greater than 0.9. This study also presented that E. aerogenes and C. sporogenes able to produce better result compared to E.coli in term of production of biohydrogen The modified Gompertz equation would be useful for further analysis of biohydrogen production performance of selected hydrogen-producing bacteria culture immobilized onto activated sponge from pineapple residues.